2020
DOI: 10.1101/2020.04.03.022434
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sleep spindles preferentially consolidate weakly encoded memories

Abstract: Sleep has been shown to be critical for memory consolidation, and recent research has demonstrated that this consolidation effect is selective, with certain memories being prioritized for strengthening. Initial strength of a memory appears to be one metric the brain uses to prioritize memory traces for sleep-based consolidation, but the role of consolidation-mediating cortical oscillations, such as sleep spindles and slow oscillations, has not been explored. Here, N=54 participants studied pairs of words to th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 110 publications
(172 reference statements)
3
32
0
Order By: Relevance
“…Our results from the DSOE data suggest that increased microstate D GEV, and the magnitude of the GEV increase, are associated with better memory for 1 PRES encoded words. These findings are in line with the plethora of research in the sleep and memory literature that indicate the prioritization of weakly encoded memories during sleep-based consolidation [Drosopoulos et al, 2007;Schapiro et al, 2017;Djonlagic et al, 2009;Denis et al, 2019;Denis et al, 2020].…”
Section: Microstate D Is Associated With Memory For 1 Pres Encoded Wosupporting
confidence: 88%
See 1 more Smart Citation
“…Our results from the DSOE data suggest that increased microstate D GEV, and the magnitude of the GEV increase, are associated with better memory for 1 PRES encoded words. These findings are in line with the plethora of research in the sleep and memory literature that indicate the prioritization of weakly encoded memories during sleep-based consolidation [Drosopoulos et al, 2007;Schapiro et al, 2017;Djonlagic et al, 2009;Denis et al, 2019;Denis et al, 2020].…”
Section: Microstate D Is Associated With Memory For 1 Pres Encoded Wosupporting
confidence: 88%
“…Sleep-based memory consolidation is selective, meaning only certain information is designated for further processing. Recent research has suggested that one contributing factor to the modulation of memory consolidation across sleep is the initial encoding strength of the memory [sleep benefits weakly encoded memories: Drosopoulos et al, 2007;Schapiro et al, 2017;Djonlagic et al, 2009;Denis et al, 2019;Denis et al, 2020;sleep benefits strongly encoded memories: Tucker and Fishbein, 2008;Schoch et al, 2017;and Wislowska et al, 2017]. In this vein, there are differing factions of evidence-some suggesting sleep benefits weakly encoded memories and others suggesting a benefit for stronger encodings.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that during sleep weaker memories receive a consolidation benefit when compared to wake where those same memories deteriorate the most. While the neurophysiological mechanism underlying this effect is unclear, recent research has shown that the consolidation of weak memories is uniquely associated with sleep spindles (Denis et al 2020;Baena et al 2020), 12-15Hz waxing and waning oscillations that are characteristic of non-rapid eye movement sleep. This builds on other evidence showing that sleep spindles facilitate memory consolidation (Schabus et al 2004;Cox et al 2012), Furthermore, memory replay in the hippocampus during quiet rest is preferential for weakly encoded memories (Schapiro et al 2018).…”
Section: Figurementioning
confidence: 99%
“…We found that stress alters the association between SWS and memory. It is notable that no associations between SWS activity and memory were found in the control group, given other research showing SWS-related benefits for both neutral and emotional episodic memory in nonstressed participants (Ackermann & Rasch, 2014;Cox et al, 2012;Denis et al, 2020;Groch et al, 2013;Mikutta et al, 2019;Niknazar et al, 2015;Payne, Chambers, et al, 2012;Payne et al, 2015;Plihal & Born, 1997). While the reason for this finding is unclear, one possible explanation may be the delay interval used in this study design.…”
Section: Discussionmentioning
confidence: 68%
“…In humans, this coordination has been demonstrated in epilepsy patients with intracranial hippocampal recordings (Staresina et al, 2015). Although hippocampal ripples cannot be detected non-invasively, slow oscillation-spindle coupling as detected via scalp EEG has been associated with memory consolidation in healthy humans (Denis et al, 2020;Mikutta et al, 2019;Niknazar et al, 2015;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 98%